Modeling Analysis and Queuing System at Mie Gacoan Restaurant - Pasaribu, Yulia Rahman; Maulana, Muhammad Vicky; Safiri, Satria Rizki; Qalbi, Salsabila; Artaviana , Dinda Natasya (Jurnal Multidisiplin Indonesia, 2025)
Mie Gacoan Restaurant faces long queues especially during rush hour, which leads to long waiting times and decreased customer satisfaction. The purpose of this study is to evaluate the existing queue system and create an overall service process model. The system receives input in the form of data on the number of customers and service duration, while the output is in the form of a queue model and performance analysis. This topic is significant because the speed of service is a key factor in customer satisfaction in fast food restaurants. Currently, there is no model that describes in detail the queuing system at Mie Gacoan, so there is no analytical basis for operational improvements. The solution is carried out through discrete simulation modeling based on the results of field observations. The system was analyzed using a single queue–multiple server model that depicts the real conditions of the restaurant. Simulation of multiple scenarios was used to examine the effect of changes in the number of servers on queue performance. The addition of one waiter during peak hours has been proven to reduce waiting times by up to 35% and queue lengths by up to 40%. This research contributes as a quantitative basis for operational decision-making.